المالكية المغاربة في المدينة المنورة ومكة المكرمة؛ دراسة في التواجد العلمي والوظيفي والمجاورة (El-Wahat Journal for Research and Studies, 2023)
ملخص:  يهدف هذا البحث إلى إبراز المكانة العلمية للمذهب المالكي من خلال تواجده التاريخي بين الحجاز والمغرب من خلال الرحلات العلمية للمالكية المغاربة طلبة ومشايخا عل مختلف مدارسهم في المذهب، سواء في القيروان أو فاس أو الأندلس آنذاك، وهذا من خلال الرحلات وما تذكره تراجم الأعلام مما يجلي المكانة لهذا المذهب والصلة المعروفة بين مكة والمدينة والمغرب العربي، و هذا البحث يقع في خطة تكمن في الوقوف على التعريف بالمدرسة المالكية المدنية، ثم في مبحث آخر يقع التعريف بالمدرستين المغربيتين وهما مدرسة القيروان في تونس وفاس في المغرب الأقصى ثم مدرسة الأندلس، وكل ذلك مع قراءة تاريخية للحضور العلمي للمغاربة طلبة أو مشايخا في المشرق العربي عموما وذكر نماذج من الرحلات الى مكة والمدينة خصوصا، مما يجلي جانبا مهما من الحضور العلمي والوظيفي لمالكية المغرب الإسلامي ممن عرفوا بالرحلة العلمية أو الدينية أو المجاورة وممن تمكنوا من مناصب كالتدريس والقضاء في المدينة المنورة أو مكة المكرمة.كلمات دالة: التواصل العلمي؛ المجاورة؛ مالكية المغرب؛ الرحلات؛ الرحلة العلمية.Abstract:This research aims to highlight the scientific status of the Maliki school through its historical presence between the Hijaz and Maghreb through the scientific trips of the Maghreb Maliki students and sheikhs to their various schools in the school of thought, whether in Kairouan, Fez or Andalusia at the time, and this is through trips and what the media’s translations mention, which shows the status This doctrine and the well-known link between Mecca, Medina, and the Arab Maghreb, and this research is located in a plan that lies in standing on the definition of the Maliki civil school, and then in another topic is the definition of the two Maghreb schools, namely, the Kairouan school in Tunisia and Fez in the Far Maghreb, then the Andalus school, and all this with a reading Historic of the scientific presence of Maghreb students or sheikhs in the Arab East in general and he mentioned examples of trips to Mecca and Medina in particular, which shows an important aspect of the scientific and functional presence of the owners of the Islamic Maghreb who were known for their scientific, religious or neighboring journey and who were able to hold positions such as teaching and judging in Medina or Mecca Al Mukarramah. Key words: scientific communication; Neighboring; ownership of Maghreb; scientific trip